Pengaruh Pemberian Cookies Jagung, Kacang Hijau, Tempe (JKT) Terhadap Perubahan Berat Badan Anak Balita Kurus Usia 24 – 59 Bulan Di Wilayah Kerja Puskesmas Tanjung Karang - Dian Septiana; Igde Narda Widiada; Susilo Wirawan; Suhaema Suhaema (Poltekkes Kemenkes Mataram, 2017)
Background. At the age of five there are many nutritional problems, both macro nutrition and micronutrient problems. One of the problems of macro nutrition faced by toddlers is underweight nutrition. The use of local food such as corn, green beans, and tempeh which is processed into flour in making cookies is expected to be used as PMT to overcome nutritional problems. Research Purposes. This study aims to determine the effect of giving corn cookies, green beans, tempeh (JKT) to changes in body weight of underweight toddlers aged 24-59 months in the working area of Tanjung Karang Health Center. Research Methods. This study is a true experiment in the laboratory and pre-experimental designs with the design of the One Group Pretest Posttest in the community. The sample in this study were thin toddlers aged 24-59 months as many as 8 people with a total sampling technique. Data collection is done by organoleptic tests (color, odor, taste, aroma, texture), ranking test to determine the treatment of cookies with the highest ranking that will be used for research in the community, and test the acceptance of cookies. To determine changes in body weight before and after the intervention, Signs Tests were conducted. Research Result. Based on the results of the hedonic test, the addition of corn flour, green bean flour and tempeh flour had an effect on the smell of cookies (P = 0.010), while the parameters of color, taste and texture were not significant (p> 0.05). The results showed no changes in body weight before and after administration of intervention (p = 0.289). The conclusion that giving JKT cookies to underweight toddlers aged 24-59 months for 14 days did not have a significant effect on changes in underweight underweight children (p> 0.05).